Surface-modified lithium-rich manganese-based positive electrode material, preparation method and lithium ion battery
By forming a double cladding layer of disordered spinel self-protection layer and a garnet-type solid electrolyte on the lithium-rich manganese-based positive electrode material, the problem of low efficiency and poor rate performance of the material during the electrochemical cycle is solved, and its electrochemical performance is significantly improved.
Patent Information
- Application Number
- CN202510036009.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-09
AI Technical Summary
Lithium-rich manganese-based positive electrode materials have the first problems of low efficiency and poor rate performance during the electrochemical cycle, which limits their application in new energy vehicles.
By fully mixing the metal oxides required for the lithium-rich manganese-based precursor, the lithium source and the garnet-type solid electrolyte, and calcining the gradient temperature in an oxidation atmosphere, a double cladding layer with the inner layer as a disordered spinel self-protection layer and the outer layer as a garnet-type solid electrolyte is formed.
The first Coulomb efficiency and rate performance of lithium-rich manganese-based cathode material is improved, and the electrochemical stability and cyclic performance of the material is enhanced.
Smart Images

Figure CN119812279A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to a surface-modified lithium-rich manganese-based positive electrode material, a preparation method and a lithium-ion battery. Background Art
[0002] The range anxiety of new energy vehicles is an important factor that restricts the large-scale promotion of new energy vehicles. Compared with negative electrode materials, the specific capacity of positive electrode materials is low, which is one of the important factors that make it difficult for lithium-ion batteries to obtain high energy density and hinder their further development. Therefore, studying and improving the specific capacity of positive electrode materials is the key to the development of lithium-ion batteries. However, traditional positive electrode materials, such as LiCoO2, LiFePO4 and LiTMO2 (TM is two or more of Ni, Co and Mn), are limited in their application in the next generation of high energy density lithium-ion batteries due to their low electrochemical capacity and actual capacity generally less than 200mAh / g. Therefore, the development of positive electrode materials with high energy density is still a great challenge. The theoretical specific capacity of lithium-rich manganese-based positive electrode material xLi2MnO3·(1-x)LiMO2 (where M=Mn, Ni, Co, 0<x<1) is as high as 300mAh / g, which is one of the most promising materials for preparing power batteries with energy density exceeding 400Wh / kg, and is expected to significantly improve the range of new energy vehicles. However, lithium-rich manganese-based cathode materials face some challenges during the electrochemical cycle, including low first coulombic efficiency and poor rate performance, which greatly hinder the commercialization of lithium-rich manganese-based cathode materials.
[0003] The low first coulombic efficiency of lithium-rich manganese-based cathode materials produces a large irreversible capacity, which reduces the actual energy density of the battery. During the first charge and discharge cycle, when the charging voltage reaches 4.5V, Li + From Li2MnO3, oxygen anions are oxidized (O 2- →O2 2- ) to achieve charge compensation. The irreversible release of lattice oxygen leads to the generation of oxygen vacancies, which reduces the migration barrier of transition metal ions and promotes the migration of transition metal cations from the transition metal layer to the Li layer, resulting in irreversible changes in the surface structure, making it impossible for the deintercalated Li to be re-intercalated into the structure. At the same time, after the first cycle of Li2MnO3 is activated, the inert Mn 4+ , resulting in a decrease in the conductivity of the material; in addition, the poor kinetic performance of the material itself also leads to poor rate performance. Therefore, low first-cycle coulombic efficiency and poor rate performance are two very critical factors that hinder the practical application of lithium-rich manganese-based positive electrode materials.
[0004] At present, surface modification and doping are mainly used to solve the application problems of lithium-rich manganese-based positive electrode materials.
[0005] For example, in some related technologies, LiNi with good thermal stability a Mn 2-a O2 (0<a≤1) is coated on the precursor of lithium-rich manganese-based positive electrode material, and then the surface-coated lithium-rich manganese-based positive electrode material is obtained by mixed lithium sintering. Although this method improves the cycle performance of lithium-rich manganese-based materials, it does not significantly improve the first coulomb efficiency.
[0006] For example, in some related technologies, a gas delithiation agent or a solid delithiation agent is used to remove part of the Li2O from the Li2MnO3 in the lithium-rich manganese-based positive electrode material, which can improve the initial coulombic efficiency of the material. However, since the use of the gas delithiation agent or the solid delithiation agent involves the recovery of harmful gases, this will increase costs in industrial production.
[0007] For example, some related technologies propose a method of pre-treating the surface of lithium-rich manganese-based materials with oxidants such as persulfate or sulfate to remove a small amount of lithium ions in advance, thereby improving the first coulombic efficiency of the lithium-rich manganese-based materials, but the cycle performance of the materials is not improved.
[0008] For example, in some related technologies, fluorine-doped lithium-rich manganese-based precursors are prepared through precipitation reactions to achieve uniform fluorine doping, inhibit structural changes on the material surface during the cycle, and improve the voltage attenuation of lithium-rich manganese-based positive electrode materials. However, this method has little effect on improving the first coulombic efficiency. Summary of the invention
[0009] The embodiments of the present application provide a surface-modified lithium-manganese-rich positive electrode material, a preparation method and a lithium-ion battery to solve the problems of low first coulombic efficiency and poor rate performance of lithium-manganese-rich positive electrode materials in the related art.
[0010] In a first aspect, a method for preparing a surface-modified lithium-rich manganese-based positive electrode material is provided, comprising:
[0011] mixing a lithium-rich manganese-based precursor, a lithium source, and a metal oxide required for a garnet-type solid electrolyte to obtain a mixture;
[0012] Under an oxidizing atmosphere, the mixture is subjected to gradient temperature calcination to obtain a surface-modified lithium-rich manganese-based positive electrode material;
[0013] The gradient temperature calcination includes: first calcining at the nucleation temperature of the lithium-rich manganese-based material, and then heating up to calcining at the nucleation temperature of the garnet-type solid electrolyte.
[0014] In some embodiments, calcining at a nucleation temperature of the lithium-rich manganese-based material includes: calcining at 700-900° C. for 8-12 hours;
[0015] Calcination at the nucleation temperature of the garnet-type solid electrolyte includes: calcining at 900-1000° C. for 4-6 hours.
[0016] In some embodiments, before calcining the lithium-rich manganese-based material at the nucleation temperature, the gradient temperature calcination further comprises: calcining at 400-600° C. for 4-8 hours.
[0017] In some embodiments, the mass fraction of the metal oxide is 1%-10% of the lithium-rich manganese-based precursor.
[0018] In some embodiments, the garnet-type solid electrolyte includes LLZO electrolyte Li7La3Zr2O 12 ,LLZAO electrolyteLi 6.23 La3Zr2A l 0.25 O 12 and LLZTO electrolyte Li 6.24 LqCy 1.4 Ta 0.6 O 12 One or more of the .
[0019] In some embodiments, the metal oxide includes a lanthanum source and a zirconium source.
[0020] In some embodiments, the lanthanum source is selected from at least one of lanthanum oxide, lanthanum nitrate, and lanthanum acetate.
[0021] In some embodiments, the zirconium source is selected from at least one of zirconium oxide, zirconium nitrate, and zirconium acetate.
[0022] In some embodiments, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate, and lithium phosphate.
[0023] In some embodiments, the lithium-rich manganese-based precursor, the lithium source, and the metal oxide required for the garnet-type solid electrolyte are mixed to obtain a mixture, specifically comprising:
[0024] Adding the metal oxides required for the garnet-type solid electrolyte into a ball milling jar, and adding a grinding aid, and ball milling;
[0025] Then, the lithium-rich manganese-based precursor is added into a ball mill, ball milled, mixed evenly, and dried to obtain a modified lithium-rich manganese-based precursor;
[0026] The modified lithium-rich manganese-based precursor is evenly mixed with a lithium source to obtain a mixture.
[0027] In some embodiments, the grinding aid is selected from at least one of methanol, ethanol, propanol, isopropanol, and N-methylpyrrolidone.
[0028] In some embodiments, the molar ratio of the total amount of transition metal elements in the lithium-rich manganese-based precursor to the lithium element in the lithium source is 1:(1.3-1.8).
[0029] In some embodiments, the steps of preparing the lithium-rich manganese-based precursor include:
[0030] The soluble nickel source, the soluble cobalt source, the soluble manganese source and deionized water are uniformly mixed to obtain a metal salt solution;
[0031] Then, the mixture is added into an alkaline solution to carry out a coprecipitation reaction, and a lithium-rich manganese-based precursor is obtained after washing and drying.
[0032] In some embodiments, the soluble nickel source is selected from at least one of nickel sulfate and its hydrate, nickel nitrate and its hydrate, nickel carbonate and its hydrate, and nickel oxide and its hydrate.
[0033] In some embodiments, the soluble cobalt source is selected from at least one of cobalt sulfate and its hydrate, cobalt nitrate and its hydrate, cobalt carbonate and its hydrate, and cobalt oxide and its hydrate.
[0034] In some embodiments, the soluble manganese source is selected from at least one of manganese sulfate and its hydrate, manganese nitrate and its hydrate, manganese carbonate and its hydrate, and manganese oxide and its hydrate.
[0035] In some embodiments, the alkaline solution is a mixed alkaline solution comprising carbonate and ammonia water.
[0036] In some embodiments, the carbonate concentration in the mixed alkaline solution of carbonate and ammonia water is 3-12 mol / L, and the NH3 concentration is 1-5 mol / L.
[0037] In some embodiments, the carbonate is at least one of sodium carbonate, potassium carbonate or sodium bicarbonate.
[0038] In some embodiments, the molar ratio of manganese in the soluble manganese source, cobalt in the soluble cobalt source and nickel in the soluble nickel source is x:y:z, wherein 0<x<7, 0≤y<2, 0<z<4.
[0039] In some embodiments, the coprecipitation reaction is carried out in a continuous stirred tank reactor at a temperature of 40-60° C., a pH value of the reaction solution of 7.5-8.0, and a stirring speed of 200-400 rpm;
[0040] The washing process is: first washing with deionized water for 2-4 times, then washing with ethanol for 2-4 times;
[0041] The drying conditions are: temperature of 80-120° C. and vacuum drying for 12-24 hours.
[0042] In the second aspect, a surface-modified lithium-rich manganese-based positive electrode material is provided, wherein the surface-modified lithium-rich manganese-based positive electrode material includes a lithium-rich manganese-based material, a disordered spinel self-protection layer coated on the surface of the lithium-rich manganese-based material, and a garnet-type solid electrolyte coated on the surface of the disordered spinel self-protection layer.
[0043] In a third aspect, a positive electrode sheet is provided, which includes the surface-modified lithium-rich manganese-based positive electrode material as described above.
[0044] In a fourth aspect, a lithium-ion battery is provided, comprising the positive electrode sheet as described above.
[0045] The beneficial effects of the technical solution provided by this application include:
[0046] The embodiment of the present application provides a surface-modified lithium-rich manganese-based positive electrode material, a preparation method and a lithium-ion battery. The present application uses a lithium-rich manganese-based precursor as a raw material, and after being fully mixed with a lithium source and a metal oxide required for a garnet-type solid electrolyte, it is sintered in an oxidizing atmosphere. The conventional synthesis method of a garnet-type solid electrolyte is similar to that of a lithium-rich manganese-based positive electrode material, and a sintering reaction is carried out at a high temperature. The difference is that the temperature required for the synthesis of a garnet-type solid electrolyte is higher than the temperature required for the synthesis of a lithium-rich manganese-based positive electrode material. Therefore, the present application utilizes the different reaction nucleation temperatures of a lithium-rich manganese-based positive electrode material and a garnet-type solid electrolyte, and the garnet-type solid electrolyte can combine the characteristics of lithium released from the surface phase of a lithium-rich manganese-based positive electrode material due to high temperature during the synthesis process, and prepares a double coating layer of a disordered spinel self-protection layer-an outer layer of a garnet-type solid electrolyte. When a nucleation reaction occurs in a garnet-type solid electrolyte, it will rob the lithium required for the synthesis of the surface of the lithium-rich manganese-based positive electrode material, which causes the lithium-rich manganese-based positive electrode material to be in a lithium-deficient environment during the synthesis process. Therefore, a disordered spinel self-protection layer is formed on the surface of the lithium-rich manganese-based positive electrode material, that is, the lithium-rich manganese-based material. This disordered spinel self-protection layer can stabilize the material surface and reduce the release of oxygen. This disordered spinel self-protection layer can enhance the oxygen framework on the material surface and stabilize the lattice oxygen, thereby improving the first coulombic efficiency and rate performance.
[0047] As a fast ion conductor, the garnet-type solid electrolyte is generated in situ on the outer surface of the disordered spinel self-protection layer. On the one hand, it has a high ionic conductivity, which can improve the lithium ion transmission efficiency of the surface-modified lithium-rich manganese-based positive electrode material, thereby improving the charge and discharge rate of the battery. On the other hand, the garnet-type solid electrolyte is relatively stable. When coated on the surface of the lithium-rich manganese-based material, it can act as a physical barrier layer to reduce the interface side reactions between the lithium-rich manganese-based material and the external electrolyte, thereby improving the cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0048] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0049] Figure 1 A flow chart of a method for preparing a surface-modified lithium-rich manganese-based positive electrode material provided in an embodiment of the present application;
[0050] Figure 2 A schematic cross-sectional view of a surface-modified lithium-rich manganese-based positive electrode material provided in an embodiment of the present application;
[0051] Figure 3 0.1C / 0.1C charge-discharge curve diagram of the lithium-rich manganese-based positive electrode material in Example 5 and Comparative Example 1 of the present application;
[0052] Figure 4 The rate diagram of 0.1C charging, 0.2C, 0.33C, 0.5C, 1C, 2C, 3C, and 0.33C discharge of the lithium-rich manganese-based positive electrode material in Example 5 and Comparative Example 1 of the present application;
[0053] Figure 5 This is a 1C charge and discharge cycle diagram of the lithium-rich manganese-based positive electrode material in Example 5 and Comparative Example 1 of the present application.
[0054] In the figure: 1. Lithium-rich manganese-based material; 2. Disordered spinel self-protection layer; 3. Garnet-type solid electrolyte. DETAILED DESCRIPTION
[0055] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0056] See also Figure 1 As shown, the present application embodiment provides a method for preparing a surface-modified lithium-rich manganese-based positive electrode material, which comprises the following steps:
[0057] 101: Mix a lithium-rich manganese-based precursor, a lithium source, and a metal oxide required for a garnet-type solid electrolyte to obtain a mixture.
[0058] 102: Under an oxidizing atmosphere, the mixture is subjected to gradient temperature calcination to obtain a surface-modified lithium-rich manganese-based positive electrode material; wherein the surface-modified lithium-rich manganese-based positive electrode material includes a lithium-rich manganese-based material, a disordered spinel self-protective layer coated on the surface of the lithium-rich manganese-based material, and a garnet-type solid electrolyte coated on the surface of the disordered spinel self-protective layer; the gradient temperature calcination includes: first calcining at the nucleation temperature of the lithium-rich manganese-based material, and then heating to calcining at the nucleation temperature of the garnet-type solid electrolyte.
[0059] The present application uses a lithium-rich manganese-based precursor as a raw material, fully mixes it with a lithium source and the metal oxide required for a garnet-type solid electrolyte, and then sinters it in an oxidizing atmosphere. The conventional synthesis method of a garnet-type solid electrolyte is similar to that of a lithium-rich manganese-based positive electrode material, and a sintering reaction is carried out at a high temperature. The difference is that the temperature required for the synthesis of a garnet-type solid electrolyte (i.e., the nucleation temperature) is higher than the temperature required for the synthesis of a lithium-rich manganese-based positive electrode material (i.e., the nucleation temperature). Therefore, the present application utilizes the different reaction nucleation temperatures of a lithium-rich manganese-based positive electrode material and a garnet-type solid electrolyte, as well as the property of a garnet-type solid electrolyte that can combine with the lithium released from the surface phase of a lithium-rich manganese-based positive electrode material due to high temperature during the synthesis process, to prepare a double coating layer with an inner layer of a disordered spinel self-protection layer and an outer layer of a garnet-type solid electrolyte, see Figure 2 The surface-modified lithium-rich manganese-based cathode material shown is a core-shell structure, with a lithium-rich manganese-based material 1 inside, a disordered spinel self-protection layer 2 in the middle, and a garnet-type solid electrolyte 3 on the outside. When the garnet-type solid electrolyte undergoes a nucleation reaction, it will rob the lithium required for the synthesis of the surface of the lithium-rich manganese-based cathode material, which causes the lithium-rich manganese-based cathode material to be in a lithium-deficient environment during the synthesis process. Therefore, a layer of disordered spinel self-protection layer is formed on the surface of the lithium-rich manganese-based cathode material, that is, the lithium-rich manganese-based material. This disordered spinel self-protection layer can stabilize the surface of the material and reduce the release of oxygen. In addition, this disordered spinel self-protection layer can enhance the oxygen framework on the surface of the material and stabilize the lattice oxygen, thereby improving the first coulomb efficiency and rate performance.
[0060] As a fast ion conductor, the garnet-type solid electrolyte is generated in situ on the outer surface of the disordered spinel self-protection layer. On the one hand, it has a high ionic conductivity, which can improve the lithium ion transmission efficiency of the surface-modified lithium-rich manganese-based positive electrode material, thereby improving the charge and discharge rate of the battery. On the other hand, the garnet-type solid electrolyte is relatively stable. When coated on the surface of the lithium-rich manganese-based material, it can act as a physical barrier layer to reduce the interface side reactions between the lithium-rich manganese-based material and the external electrolyte, thereby improving the cycle performance.
[0061] In addition, the gradient high-temperature solid-phase synthesis method used in the present application is compatible with the existing production process, does not require additional steps, and the preparation method is simple, which is conducive to large-scale production.
[0062] During the gradient temperature calcination, the heating rate is 3-8°C / min; calcination at the nucleation temperature of the lithium-rich manganese-based material includes: calcination at 700-900°C for 8-12h; calcination at the nucleation temperature of the garnet-type solid electrolyte includes: calcination at 900-1000°C for 4-6h.
[0063] That is, in the gradient temperature calcination process, a lithium-rich manganese-based positive electrode material, i.e., a lithium-rich manganese-based material, is first synthesized in the temperature range of 700-900°C, and then the temperature is increased to 900-1000°C at a heating rate of 3-8°C / min to synthesize a garnet-type solid electrolyte. The lithium that is easily released from the near-surface of the lithium-rich manganese-based positive electrode material is snatched away, and due to the lack of lithium near the surface, a double coating layer of an inner disordered spinel self-protection layer-an outer garnet-type solid electrolyte is formed on the surface of the lithium-rich manganese-based positive electrode material.
[0064] It is precisely by utilizing the difference in nucleation temperature between the lithium-rich manganese-based material and the garnet-type solid electrolyte that a double coating layer is formed during gradient temperature calcination. The disordered spinel self-protection layer has a three-dimensional cation disordered skeleton structure, which can stabilize the valence change reaction of lattice oxygen in the lithium-rich material and inhibit oxygen release. The outer fast ion conductor garnet-type solid electrolyte can improve the transmission efficiency of lithium ions and enhance the rate performance of the material. At the same time, since the fast ion conductor is generated in situ on the disordered spinel self-protection layer, there are multi-point island contacts between the two. During the electrochemical cycle, lithium ions will diffuse from the garnet-type solid electrolyte (it can be understood that the above-mentioned in situ grown garnet-type solid electrolyte is a lithium ion solid electrolyte, that is, it has lithium ions) to the internal lithium-rich manganese-based positive electrode material for electrochemical lithium supplementation, inhibiting the irreversible phase change of the lithium-rich manganese-based positive electrode material, improving its first coulomb efficiency, inhibiting voltage decay, and greatly improving the cycle stability.
[0065] The oxidizing atmosphere is air or oxygen.
[0066] Furthermore, before calcining at the nucleation temperature of the lithium-rich manganese-based material, the gradient temperature calcination also includes: calcining at 400-600°C for 4-8h. The purpose of setting this step of low-temperature sintering is to: remove moisture and volatile substances to prevent the generation of gas during the subsequent high-temperature sintering process, which affects the material structure and performance; pre-calcination helps the precursor and the lithium source to undergo a preliminary solid-phase reaction to form the desired crystalline structure; promote the uniformity of the material; and reduce the subsequent high-temperature sintering time.
[0067] In the above step 101, the garnet-type solid electrolyte includes LLZO electrolyte Li7La3Zr2O 12 ,LLZAO electrolyteLi 6.23 La3Zr2Al 0.25 O 12and LLZTO electrolyte Li 6.24 Ln3Z 1.4 Ta 0.6 O 12 One or more of the .
[0068] It can be seen that the metal oxide of the garnet-type solid electrolyte includes at least a lanthanum source and a zirconium source.
[0069] For example, Li7La3Zr2O is the electrolyte of LLZO 12 When the metal oxide comprises a lanthanum source and a zirconium source.
[0070] For example, for LLZAO electrolyte Li 6.23 La3Zr2A l 0.25 O 12 When the metal oxide is used, it includes not only a lanthanum source and a zirconium source, but also an aluminum source such as alumina.
[0071] For example, for LLZTO electrolyte Li 6.24 Ln3Z 1.4 Ta 0.6 O 12 When the metal oxide is used, it includes not only a lanthanum source and a zirconium source, but also a tantalum source, such as tantalum pentoxide.
[0072] When the materials are taken and mixed, the mass fraction of the metal oxide is 1%-10% of the lithium-rich manganese-based precursor.
[0073] For example, as an example, the garnet-type solid electrolyte is LLZO electrolyte Li7La3Zr2O 12 When the metal oxide comprises a lanthanum source and a zirconium source, the lanthanum source and the zirconium source are mixed in a molar ratio of 3:2, and the total mass of the lanthanum source and the zirconium source is 1%-10% of the lithium-rich manganese-based precursor.
[0074] The lanthanum source is selected from at least one of lanthanum oxide, lanthanum nitrate and lanthanum acetate.
[0075] The zirconium source is selected from at least one of zirconium oxide, zirconium nitrate and zirconium acetate.
[0076] The above step 101, mixing the lithium-rich manganese-based precursor, the lithium source and the metal oxide required for the garnet-type solid electrolyte to obtain a mixture, specifically includes the following steps:
[0077] 201: Add the metal oxides required for the garnet-type solid electrolyte into a ball mill, add a grinding aid, and perform ball milling.
[0078] In step 201, the grinding aid is selected from at least one of methanol, ethanol, propanol, isopropanol and N-methylpyrrolidone. The rotation speed of the ball milling process is 300-600 rpm.
[0079] 202: The lithium-rich manganese-based precursor is then added to a ball mill, ball milled, mixed evenly, and dried to obtain a modified lithium-rich manganese-based precursor.
[0080] In step 202, the rotation speed of the ball milling process is 300-500 rpm.
[0081] The drying conditions are: vacuum drying at a temperature of 100-120°C for 6-20 hours.
[0082] 203: The modified lithium-rich manganese-based precursor is mixed evenly with a lithium source to obtain a mixture.
[0083] In step 203, the molar ratio of the total amount of transition metal elements in the lithium-rich manganese-based precursor to the lithium element in the lithium source is 1:(1.3-1.8). The transition metal elements in the lithium-rich manganese-based precursor include nickel, manganese and cobalt.
[0084] In the above step 101, the steps of preparing the lithium-rich manganese-based precursor include:
[0085] 301: Evenly mix a soluble nickel source, a soluble cobalt source, a soluble manganese source and deionized water to obtain a metal salt solution.
[0086] In step 301, the soluble nickel source is selected from at least one of nickel sulfate and its hydrate, nickel nitrate and its hydrate, nickel carbonate and its hydrate, and nickel oxide and its hydrate.
[0087] The soluble cobalt source is selected from at least one of cobalt sulfate and its hydrate, cobalt nitrate and its hydrate, cobalt carbonate and its hydrate, and cobalt oxide and its hydrate.
[0088] The soluble manganese source is at least one selected from manganese sulfate and its hydrate, manganese nitrate and its hydrate, manganese carbonate and its hydrate, manganese oxide and its hydrate.
[0089] The molar ratio of manganese element in the soluble manganese source, cobalt element in the soluble cobalt source and nickel element in the soluble nickel source is x:y:z, wherein 0<x<7, 0≤y<2, 0<z<4.
[0090] For example, as an example, when the molar ratio of manganese:cobalt:nickel is 0.675:0.1625:0.1625, the disordered spinel self-protection layer obtained is Li 1.2-x Ni 0.13+x Co 0.13 Mn 0.54 O2,0 <x<0.1。
[0091] By changing the ratio of transition metal elements in the lithium-rich manganese-based precursor, the composition of the disordered spinel self-protection layer can be adjusted.
[0092] 302: Adding it into an alkaline solution to carry out a co-precipitation reaction, and obtaining a lithium-rich manganese-based precursor after washing and drying.
[0093] In step 302, the alkaline solution is a mixed alkaline solution containing carbonate and ammonia water.
[0094] Wherein, the carbonate concentration in the mixed alkaline solution of carbonate and ammonia water is 3-12 mol / L, and the NH3 concentration is 1-5 mol / L.
[0095] The carbonate is at least one of sodium carbonate, potassium carbonate or sodium bicarbonate.
[0096] The coprecipitation reaction is carried out in a continuous stirred tank reactor at a temperature of 40-60° C., a pH value of the reaction solution of 7.5-8.0, and a stirring speed of 200-400 rpm.
[0097] The washing process is: first washing with deionized water for 2-4 times, and then washing with ethanol for 2-4 times to prevent excess carbonate and ammonia from remaining.
[0098] The drying conditions are: temperature of 80-120° C. and vacuum drying for 12-24 hours.
[0099] The present application also provides a surface-modified lithium-rich manganese-based positive electrode material, wherein the surface-modified lithium-rich manganese-based positive electrode material comprises a lithium-rich manganese-based material, a disordered spinel self-protection layer coated on the surface of the lithium-rich manganese-based material, and a garnet-type solid electrolyte coated on the surface of the disordered spinel self-protection layer. It is understood that it can be prepared by any of the above-described surface-modified lithium-rich manganese-based positive electrode material preparation methods.
[0100] An embodiment of the present application also provides a positive electrode sheet, which includes the surface-modified lithium-rich manganese-based positive electrode material as described above.
[0101] An embodiment of the present application also provides a lithium-ion battery, which includes the positive electrode sheet as described above.
[0102] The present application is described in detail below through several embodiments.
[0103] Example 1
[0104] Step (1), dissolve MnSO4·H2O, CoSO4·7H2O and NiSO4·6H2O in 3L of deionized water according to the molar ratio of manganese element, cobalt element and nickel element of 0.675:0.1625:0.1625, stir evenly to form a metal salt solution, and pump it into a continuous stirred tank reactor (CSTR) at a rate of 100ml / h. Weigh 6mol of anhydrous sodium carbonate to prepare 3L of solution as a precipitant, and add 0.3mol / L of ammonia water as a complexing agent. Adjust the pH value of CSTR to about 7.75. After the reaction is completed, filter, wash and dry to obtain a lithium-rich manganese-based precursor (Ni 1 / 6 Co 1 / 6 Mn 4 / 6 CO3).
[0105] Step (2), add La2O3 and ZrO2 equivalent to 1% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0106] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 900°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0107] Example 2
[0108] Step (1) is the same as in Example 1.
[0109] Step (2), add La2O3 and ZrO2 equivalent to 3% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0110] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 900°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0111] Example 3
[0112] Step (1) is the same as in Example 1.
[0113] Step (2), add La2O3 and ZrO2 equivalent to 5% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0114] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 900°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0115] Example 4
[0116] Step (1) is the same as in Example 1.
[0117] Step (2), add La2O3 and ZrO2 equivalent to 1% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0118] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 950°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0119] Example 5
[0120] Step (1) is the same as in Example 1.
[0121] Step (2), add La2O3 and ZrO2 equivalent to 3% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0122] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 950°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0123] Example 6
[0124] Step (1) is the same as in Example 1.
[0125] Step (2), add La2O3 and ZrO2 equivalent to 5% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0126] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 950°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0127] Example 7
[0128] Step (1) is the same as in Example 1.
[0129] Step (2), add La2O3 and ZrO2 equivalent to 1% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0130] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 1000°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0131] Example 8
[0132] Step (1) is the same as in Example 1.
[0133] Step (2), add La2O3 and ZrO2 equivalent to 3% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0134] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 1000°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0135] Example 9
[0136] Step (1) is the same as in Example 1.
[0137] Step (2), add La2O3 and ZrO2 equivalent to 5% mass fraction of the surface modified lithium-rich manganese-based positive electrode material according to the molar ratio of lanthanum element to zirconium element of 3:2 into a ball mill, add an appropriate amount of ethanol, and ball mill at a speed of 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) into the ball mill, ball mill at a speed of 400r / min for 5h, mix well and dry to obtain a modified lithium-rich manganese-based precursor.
[0138] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, ball milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere and keeping warm for 5h, then heating to 850°C at 5°C / min and keeping warm for 10h, and finally heating to 1000°C at 5°C / min and keeping warm for 5h, to prepare a surface-modified lithium-rich manganese-based positive electrode material.
[0139] Comparative Example 1
[0140] Step (1) is the same as in Example 1.
[0141] Step (2), adding the lithium-rich manganese-based precursor obtained in step (1) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere for 5h, and then heating to 850°C at a heating rate of 5°C / min for 10h, to prepare a lithium-rich manganese-based positive electrode material Li without surface modification. 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0142] Comparative Example 2
[0143] Step (1) is the same as in Example 1.
[0144] Step (2), adding the lithium-rich manganese-based precursor obtained in step (1) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere for 5h, then heating to 850°C at a heating rate of 5°C / min for 10h, and finally heating to 900°C at a heating rate of 5°C / min for 5h, to prepare a lithium-rich manganese-based positive electrode material Li only sintered by gradient sintering 1.2 Ni 0.13 Co 0.13 Mn 0.54 O2.
[0145] Comparative Example 3
[0146] Step (1) is the same as in Example 1.
[0147] Step (2), adding Li7La3Zr2O equivalent to 3% by mass of lithium-rich manganese-based positive electrode material 12 Add to the ball mill, add appropriate amount of ethanol, and ball mill at 500r / min for 4h. Then add the lithium-rich manganese-based precursor obtained in step (1) to the ball mill, ball mill at 400r / min for 5h, mix well and dry to obtain the modified lithium-rich manganese-based precursor.
[0148] Step (3), adding the modified lithium-rich manganese-based precursor obtained in step (2) and Li2CO3 in a ratio of transition metal element to lithium element of 1:1.5 into a ball mill, milling at a speed of 400r / min for 4h, mixing evenly, and then placing in a muffle furnace, heating to 500°C at a heating rate of 5°C / min in an air atmosphere for 5h, and then heating to 850°C at a heating rate of 5°C / min for 10h, to prepare a coating only with Li7La3Zr2O 12 Lithium-rich manganese-based positive electrode materials.
[0149] Electrical performance testing and analysis
[0150] The lithium-rich manganese-based positive electrode materials obtained in the above embodiments and comparative examples were respectively weighed with a conductive agent (acetylene black) and a binder (polyvinylidene fluoride) in a mass ratio of 80:10:10, and then an appropriate amount of NMP (N-methylpyrrolidone) was added and mixed evenly. The prepared slurry was evenly coated on an aluminum foil and placed in a vacuum drying oven at 80°C for 12 hours. After drying, the cut pieces were taken out and rolled, and the pressed electrode pieces were placed in a vacuum drying oven at 120°C for 8 hours to obtain the lithium-rich manganese-based positive electrode electrode pieces of the present invention.
[0151] Button cells were prepared in a glove box with oxygen and water contents less than 0.01 ppm and assembled according to the R2032 button cell structure. The negative electrode was metallic lithium, the separator was Celgard 2400 porous polyethylene separator, and the electrolyte was EC-based and PC-based electrolyte.
[0152] Carry out 0.1C charge and discharge at 25℃ and voltage range of 2.0-4.6V. Carry out 0.1C charge at 25℃ and voltage range of 2.0-4.6V, and then carry out 0.2C, 0.33C, 0.5C, 1C, 2C, 3C, and 0.33C discharge for rate test. Carry out 100 cycles of 1C charge and discharge at 25℃ and voltage range of 2.0-4.6V.
[0153] Among them, under the test conditions of test temperature of 25°C, current density of 0.1C (1C = 220mAh / g), charge and discharge voltage of 2.0-4.6V, Figure 3 It is a comparison chart of the charge and discharge curves of Example 5 and Comparative Example 1. The first discharge specific capacity of Example 5 is 263.5 mAh / g, and the first efficiency is 93.64%; while the first discharge specific capacity of Comparative Example 1 is 242.38 mAh / g, and the first efficiency is 78.45%.
[0154] Figure 4 The rate performance comparison diagram of Example 5 and Comparative Example 1 shows that the discharge capacities of Example 5 at the charge rate of 0.1C, the discharge rates of 0.2C, 0.33C, 0.5C, 1C, 2C, 3C, and 0.33C are 262.92 mAh / g, 259.0 mAh / g, 247.91 mAh / g, 234.63 mAh / g, 221.93 mAh / g, 209.72 mAh / g, and 252 .17mAh / g; while the discharge capacities of Comparative Example 1 at charging rates of 0.1C and discharging rates of 0.2C, 0.33C, 0.5C, 1C, 2C, 3C, and 0.33C are 243.96mAh / g, 237.22mAh / g, 225.26mAh / g, 208.08mAh / g, 187.63mAh / g, 164.76mAh / g, and 228.88mAh / g, respectively.
[0155] Figure 5 The figure is a comparison of the cycle performance of Example 5 and Comparative Example 1. The capacity retention rate of Example 5 after 100 cycles at 1C rate is 92.85%, while that of Comparative Example 1 is 75.63%. The following are the test results of all the examples and comparative examples:
[0156] Table 1 Power-off test results
[0157]
[0158] It can be seen from Table 1 that the first coulombic efficiency and the first discharge capacity of Example 1-9 are significantly higher than those of Comparative Example 1-3, the discharge capacity of Example 1-9 at a current density of 3C is significantly higher than that of Comparative Example 1-3, and the 100-cycle capacity retention rate of Example 1-9 is significantly higher than that of Comparative Example 1-3. This fully demonstrates that the inner layer disordered spinel self-protection layer-outer layer Li7La3Zr2O 12 The double coating layer of garnet-type solid electrolyte can significantly improve the electrochemical performance of lithium-rich manganese-based positive electrode.
[0159] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A method for preparing a surface-modified lithium-rich manganese-based positive electrode material, characterized in that: It includes: mixing a lithium-rich manganese-based precursor, a lithium source, and a metal oxide required for a garnet-type solid electrolyte to obtain a mixture; Under an oxidizing atmosphere, the mixture is subjected to gradient temperature calcination to obtain a surface-modified lithium-rich manganese-based positive electrode material; The gradient temperature calcination includes: first calcining at the nucleation temperature of the lithium-rich manganese-based material, and then heating up to calcining at the nucleation temperature of the garnet-type solid electrolyte.
2. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: Calcination at a nucleation temperature of the lithium-rich manganese-based material includes: calcining at 700-900° C. for 8-12 hours; Calcination at the nucleation temperature of the garnet-type solid electrolyte includes: calcining at 900-1000° C. for 4-6 hours.
3. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: Before calcining at the nucleation temperature of the lithium-rich manganese-based material, the gradient temperature calcination further comprises: calcining at 400-600° C. for 4-8 hours.
4. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The mass fraction of the metal oxide is 1%-10% of the lithium-rich manganese-based precursor.
5. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The garnet-type solid electrolyte includes LLZO electrolyte Li7La3Zr2O 12 ,LLZAO electrolyteLi 6.23 La3Zr2Al 0.25 O 12 and LLZTO electrolyte Li 6.24 LqCy 1.4 Ta 0.6 O 12 One or more of the .
6. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The metal oxide includes a lanthanum source and a zirconium source.
7. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 6, characterized in that: The lanthanum source is selected from at least one of lanthanum oxide, lanthanum nitrate and lanthanum acetate.
8. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 6, characterized in that: The zirconium source is selected from at least one of zirconium oxide, zirconium nitrate and zirconium acetate.
9. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The lithium source is selected from at least one of lithium carbonate, lithium hydroxide, lithium nitrate, lithium acetate and lithium phosphate.
10. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The lithium-rich manganese-based precursor, the lithium source and the metal oxide required for the garnet-type solid electrolyte are mixed to obtain a mixture, specifically comprising: Add the metal oxides required for the garnet-type solid electrolyte into a ball milling jar, add a grinding aid, and perform ball milling; Then, the lithium-rich manganese-based precursor is added into a ball mill, ball milled, mixed evenly, and dried to obtain a modified lithium-rich manganese-based precursor; The modified lithium-rich manganese-based precursor is evenly mixed with a lithium source to obtain a mixture.
11. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 10, characterized in that: The grinding aid is selected from at least one of methanol, ethanol, propanol, isopropanol and N-methylpyrrolidone.
12. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 10, characterized in that: The molar ratio of the total amount of transition metal elements in the lithium-rich manganese-based precursor to the lithium element in the lithium source is 1:(1.3-1.8).
13. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The steps of preparing the lithium-rich manganese-based precursor include: The soluble nickel source, the soluble cobalt source, the soluble manganese source and deionized water are uniformly mixed to obtain a metal salt solution; Then, the mixture is added into an alkaline solution to carry out a coprecipitation reaction, and a lithium-rich manganese-based precursor is obtained after washing and drying.
14. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 13, characterized in that: The soluble nickel source is selected from at least one of nickel sulfate and its hydrate, nickel nitrate and its hydrate, nickel carbonate and its hydrate, and nickel oxide and its hydrate.
15. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 13, characterized in that: The soluble cobalt source is selected from at least one of cobalt sulfate and its hydrate, cobalt nitrate and its hydrate, cobalt carbonate and its hydrate, and cobalt oxide and its hydrate.
16. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 13, characterized in that: The soluble manganese source is at least one selected from manganese sulfate and its hydrate, manganese nitrate and its hydrate, manganese carbonate and its hydrate, manganese oxide and its hydrate.
17. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 13, characterized in that: The alkaline solution is a mixed alkaline solution containing carbonate and ammonia water.
18. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 17, characterized in that: The carbonate concentration in the mixed alkaline solution of carbonate and ammonia water is 3-12 mol / L, and the NH3 concentration is 1-5 mol / L.
19. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 17, characterized in that: The carbonate is at least one of sodium carbonate, potassium carbonate or sodium bicarbonate.
20. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 13, characterized in that: The molar ratio of manganese element in the soluble manganese source, cobalt element in the soluble cobalt source and nickel element in the soluble nickel source is x:y:z, wherein 0<x<7, 0≤y<2, 0<z<4.
21. The method for preparing the surface-modified lithium-rich manganese-based positive electrode material according to claim 13, characterized in that: The coprecipitation reaction is carried out in a continuous stirred tank reactor at a temperature of 40-60°C, a pH value of the reaction solution of 7.5-8.0, and a stirring speed of 200-400 rpm; The washing process is: first washing with deionized water for 2-4 times, then washing with ethanol for 2-4 times; The drying conditions are: temperature of 80-120° C. and vacuum drying for 12-24 hours.
22. A surface-modified lithium-rich manganese-based positive electrode material, characterized in that: The surface-modified lithium-rich manganese-based positive electrode material includes a lithium-rich manganese-based material, a disordered spinel self-protection layer coated on the surface of the lithium-rich manganese-based material, and a garnet-type solid electrolyte coated on the surface of the disordered spinel self-protection layer.
23. A positive electrode sheet, characterized in that: It includes the surface-modified lithium-rich manganese-based positive electrode material as claimed in claim 22.
24. A lithium ion battery, characterized in that: It includes the positive electrode sheet as claimed in claim 23.
Citation Information
Patent Citations
Lithium-enriched manganese-based anode material with fast ion conductor coating layer and surface heterostructure and preparation method of lithium-enriched manganese-based anode material
CN103928664A
Method for coating anode material with ion-electron mixed electronic conducting garnet structure
CN109524654A
Lithium ion battery composite positive electrode material and preparation method thereof
CN115588733A
Solid electrolyte coated and modified positive electrode material as well as preparation method and application thereof
CN116014142A
Nonaqueous electrolyte battery, battery pack and vehicle
US20180083279A1
Cited By
Modification method of lithium-rich manganese-based solid solution lithium ion battery positive electrode material
CN120089732A
A modification method for lithium-rich manganese-based solid solution lithium-ion battery positive electrode material
CN120089732B
Composite positive electrode material with sodium-oxygen permeable layer as well as preparation method and application of composite positive electrode material
CN121282142A
Lithium-rich manganese-based positive electrode material, preparation method, positive plate and sulfide solid-state battery
CN121929756A
Lithium-rich manganese-based positive electrode material, preparation method, positive electrode sheet, and sulfide solid-state battery
CN121929756B